EFFECT OF CIPLUKAN STEMS AND LEAVES EXTRACT ADMINISTRATION (Physalis angulata L.) ON THE DEGREE OF hepatic lobes INFLAMMATION IN DYSLIPIDEMIA INDUCED WISTAR RATS - Safira, Nazala; Pamungkas, Katon; Utami, Rizki fajar; Ahsani, Dwi Nur; Pramaningtyas, Miranti Dewi (Universitas Syiah Kuala, 2024)
The aim of this study was to determine the effect of stems and leaves ciplukan extract on the degree of liver lobe inflammation in dyslipidemia-induced wistar rats. This research was an experimental study with a post-test only design. A total of 24 Wistar rats were allotted into 4 groups with 6 rats per group. Hepatic organs were then histologically stained with Hematoxylin-Eosin stain. Inflammation reading was done by looking for inflammatory foci in the preparation. The result was then analyzed using Kruskal-Wallis test. The results showed that groups I and II had one severe inflammation. Group III had two severe degrees of inflammation. Group IV had no severe inflammation. The analysis revealed that there was no significant difference in the degree of inflammation between groups (P= 0.964). Administration of ciplukan stem and leaf extract did not affect the degree of liver lobe inflammation in Wistar rats induced by dyslipidemia.